Surface-tackified heat-conducting gasket as well as preparation method and application thereof

By adding MQ silicone resin and other silicone oils to the thermal pad, the problem of balancing thermal conductivity and surface viscosity is solved, achieving the unification of high thermal conductivity and suitable surface viscosity, improving production efficiency and use quality.

CN119351062APending Publication Date: 2025-01-24SHENZHEN DEYIMENG ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411470260.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

While improving thermal conductivity, existing thermal gaskets often lead to reduced surface viscosity, affecting the quality of use and production efficiency.

Method used

By adding MQ silicone resin to the thermal pad, combined with vinyl silicone oil and hydrogen-containing silicone oil, the viscosity and chemical structure are adjusted to directly enhance the surface stickiness of the thermal pad.

Benefits of technology

While maintaining the high thermal conductivity, the heating pads improve the surface viscosity, ensure the stability and efficiency of the assembly, and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005094495250000031
    Figure BDA0005094495250000031
  • Figure BDA0005094495250000071
    Figure BDA0005094495250000071
  • Figure BDA0005094495250000072
    Figure BDA0005094495250000072
Patent Text Reader

Abstract

The invention discloses a surface-tackified heat-conducting gasket as well as a preparation method and application thereof, and the surface-tackified heat-conducting gasket is prepared from the following components in parts by weight: 2 to 8 parts of vinyl silicone oil, 0.5 to 3 parts of MQ silicon resin, 0.15 to 0.45 part of hydrogen-containing silicone oil, 0.1 to 0.25 part of an inhibitor, 0.08 to 0.2 part of a catalyst and 89 to 95.5 parts of heat-conducting powder. The heat-conducting gasket has the advantages of high heat-conducting property, proper surface viscosity, simple preparation process and low production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal interface materials, and in particular to a surface-adhesive thermally conductive pad and a preparation method and application thereof. Background Art

[0002] With the advent of the 5G era, electronic components are developing towards high power and miniaturization, and at the same time, the heat generation of electronic components has increased significantly. If the heat cannot be discharged in time, the temperature of the electronic components will rise rapidly, and it is very easy to be damaged. Studies have shown that the life of electronic components will decrease by 10% for every 2°C increase in temperature. Thermally conductive gaskets are widely used because of their high thermal conductivity, high insulation, shock absorption, double-sided self-adhesiveness and other properties that are superior to other thermal interface materials. At present, thermally conductive gaskets with a thermal conductivity of 1-2W / mK can no longer meet the industry's thermal conductivity needs, and it is necessary to study thermally conductive gaskets with higher thermal conductivity. However, since high thermal conductivity thermally conductive gaskets are often made of organic silicone rubber compounded with a large amount of thermally conductive powder, and the content of thermally conductive powder is as high as 90% or more, it will also seriously affect the surface viscosity of the thermally conductive gasket. The surface viscosity of the thermally conductive gasket is mainly provided by the organic phase of thermally conductive silicone, which bonds the thermally conductive powder and then provides the surface viscosity of the thermally conductive gasket. The compounding of a large amount of thermally conductive powder will cause its surface viscosity to become lower and lower. The level of surface viscosity often affects the quality of use by customers. If the viscosity is too high, the powder will stick to the release film when the thermal pad is torn off, resulting in poor appearance and thermal conductivity of the thermal pad. If the viscosity is too high, it will make the customer's hands or manipulator sticky when using it, which is not conducive to use; if the viscosity is too low, it will easily fall off after assembly, causing rework and increasing costs and affecting efficiency. At present, there is a solution to adjust the viscosity of the gasket surface by adding a layer or double layer of thermal conductive coating to the surface of the thermal conductive gasket, and at the same time reduce the impact of the thermal conductivity caused by the coating by changing the surface area of ​​the coating. However, this solution adds production processes in the actual application process, and the surface area of ​​the coating is difficult to control evenly, which is prone to defects and increases production costs. In addition, the surface of the thermal conductive gasket is partially coated and partially uncoated, resulting in an uneven surface of the thermal conductive gasket. When in use, the uncoated part is prone to air, which increases the interface thermal resistance and does not give full play to the thermal conductivity of the thermal conductive gasket. It can be seen that for thermal conductive gaskets, it is often difficult to balance high thermal conductivity and appropriate surface viscosity.

[0003] Therefore, it is urgent to produce a thermally conductive gasket with moderate viscosity and high thermal conductivity for the convenience of customers. Summary of the invention

[0004] In view of the defects in the prior art, the present invention provides a thermally conductive gasket with surface adhesion enhancement, and a preparation method and application thereof.

[0005] The present invention provides a surface-adhesive thermally conductive pad, which comprises the following components by weight: 2-8 parts of vinyl silicone oil, such as 2, 3, 4, 5, 6, 7, and 8 parts; 0.5-3 parts of MQ silicone resin, such as 0.5, 1, 1.5, 2, 2.5, and 3 parts; 0.15-0.45 parts of hydrogen-containing silicone oil, such as 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, and 0.45 parts; 0.1-0.25 parts of inhibitor, such as 0.1, 0.15, 0.2, and 0.25 parts; 0.08-0.2 parts of catalyst, such as 0.08, 0.1, 0.12, 0.15, 0.18, and 0.2 parts; 89-95.5 parts of thermally conductive powder, such as 89, 89.5, 90, 92, 93.5, 95, and 95.5 parts;

[0006] The vinyl content of the vinyl silicone oil is 0.3%-1%, and the hydrogen content of the hydrogen-containing silicone oil is 0.1%-0.18%.

[0007] The MQ silicone resin added in the present invention can reduce the viscosity of the system, improve production efficiency and improve product yield. At the same time, the MQ silicone resin structure contains a large number of hydroxyl groups, which can be used as reactive groups to chemically react with adherends for bonding. By directly adding MQ silicone resin to enhance the surface viscosity of the thermally conductive gasket, the manufacturing process is simple, the defective product rate will not be increased due to multiple processes, and the manufacturing cost is reduced.

[0008] The thermally conductive gasket of the present invention can simultaneously enhance the thermal conductivity and surface viscosity of the thermally conductive gasket, can realize automated use by downstream customers, and improve customer use efficiency.

[0009] Furthermore, the vinyl silicone oil is any one or more combinations of double-terminal vinyl silicone oil, single-terminal vinyl silicone oil, and end-side vinyl silicone oil, preferably double-terminal vinyl silicone oil.

[0010] Furthermore, the viscosity of the vinyl silicone oil is 100-1000 mPa·s, such as 100, 200, 400, 600, 800, 1000 mPa·s.

[0011] Furthermore, the chemical structural formula of the MQ silicone resin is as follows:

[0012]

[0013] Wherein, R is any one or more of vinyl, phenyl, hydrogen or methyl, that is, the MQ silicone resin can be any one or more of hydroxyvinyl MQ silicone resin, hydroxyphenyl MQ silicone resin, hydroxymethyl MQ silicone resin, hydroxyMQ silicone resin, etc., preferably hydroxyvinyl MQ silicone resin, because it contains hydroxyl groups and vinyl groups, and the vinyl groups can undergo hydrosilylation reaction with the hydrogen-containing silicone oil in the system, so that the MQ silicone resin is not easily separated from the silica gel.

[0014] Furthermore, the hydrogen-containing silicone oil is any one or more combinations of terminal hydrogen-containing silicone oil and side hydrogen-containing silicone oil, and preferably the terminal hydrogen-containing silicone oil and the side hydrogen-containing silicone oil are mixed in a mass ratio of 1:(0.8-1.2).

[0015] Furthermore, the thermally conductive powder is any one or more combinations of aluminum oxide, aluminum hydroxide, aluminum nitride, and boron nitride, preferably a combination of thermally conductive powders of different particle sizes and shapes, more preferably quasi-spherical aluminum oxide with a D50 of 4-6 μm, spherical aluminum oxide with a D50 of 39-42 μm, and spherical aluminum oxide with a D50 of 69-72 μm, which are compounded in a mass ratio of (38-42):(28-32):(28-32); Alternatively, quasi-spherical alumina with a D50 of 1-2 μm, spherical aluminum nitride with a D50 of 4-6 μm, spherical alumina with a D50 of 38-42 μm, spherical alumina with a D50 of 89-91 μm, and spherical alumina with a D50 of 99-102 μm are compounded in the mass ratio of (13-17):(28-32):(23-27):(18-22):(8-12), and the thermal conductive powder combination is preferably the latter.

[0016] Furthermore, the mass ratio of the vinyl silicone oil to the MQ silicone resin is 1:(0.12-0.4).

[0017] Furthermore, the mass ratio of the vinyl silicone oil to the MQ silicone resin is 1:(0.28-0.35).

[0018] Furthermore, the inhibitor is a cyclohexanol inhibitor, such as ethynyl cyclohexanol.

[0019] Furthermore, the catalyst is a platinum catalyst.

[0020] The present invention also provides a method for preparing the thermally conductive pad, comprising the following steps:

[0021] The components other than the catalyst are weighed and mixed evenly according to weight, and finally the catalyst is added and mixed evenly, and after vacuuming, the surface-adhesive thermal conductive pad is obtained by calendering and baking;

[0022] The vacuuming time is 0.5-2 hours, and the baking is carried out at 120-150° C. for 0.5-1 hour.

[0023] The present invention manufactures the thermal conductive pad through a one-step method, which can increase the surface viscosity of the thermal conductive pad without reducing other properties, has no redundant steps, is simple in process and is low in price.

[0024] The invention also provides application of the thermally conductive pad in electronic appliances and automobile manufacturing.

[0025] The present invention is particularly suitable for thermally conductive gaskets with one side reinforced with a substrate such as PI film, silicone cloth, or PET film, with the substrate facing downward. It is only necessary to tear off the release film on the surface of the thermally conductive gasket, place it in a positioning fixture, and put the part to which the thermally conductive gasket needs to be pasted in the positioning fixture, so that the thermally conductive gasket can be easily installed in the part, greatly improving the production efficiency of the product.

[0026] In summary, compared with the prior art, the present invention achieves the following technical effects:

[0027] (1) The thermally conductive gasket provided by the present invention can simultaneously achieve high thermal conductivity and suitable surface viscosity;

[0028] (2) The thermally conductive gasket provided by the present invention has a high 90° peeling force with the surface of the original film and is not easy to fall off after assembly;

[0029] (3) The thermal conductive gasket preparation method provided by the present invention has a simple process and can reduce production costs. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0031] Example

[0032] The present invention is further described below in conjunction with specific examples and comparative examples. The following specific examples are all preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following examples, and are particularly not limited to the types of the various component raw materials used in the following specific examples.

[0033] 1. The sources of raw materials for the embodiments and comparative examples are as follows:

[0034] Vinyl silicone oil #1: double-terminal vinyl silicone oil, viscosity 1000 mPa·s, brand RH-VI1000E, Zhejiang Runhe Silicone New Materials Co., Ltd.

[0035] Vinyl silicone oil #2: double-terminal vinyl silicone oil, viscosity 100 mPa·s, brand VS-100P, Shanghai Jingri New Material Technology Co., Ltd.;

[0036] MQ silicone resin #1: hydroxy vinyl MQ silicone resin, brand SH-5202S, Hubei Longsheng Sihai New Materials Co., Ltd.;

[0037] MQ silicone resin #2: hydroxyphenyl MQ silicone resin, brand SH-1040, Hubei Longsheng Sihai New Materials Co., Ltd.;

[0038] Hydrogenated silicone oil #1: Hydrogenated silicone oil, with a hydrogen content of 0.1 wt%, brand H-202L, produced by Jiangxi Haiduo Organic Silicone Materials Co., Ltd.

[0039] Hydrogenated silicone oil #2: terminal hydrogenated silicone oil, hydrogen content is 0.18wt%, brand name HD-202L, Jiangxi Haiduo Silicone Materials Co., Ltd.;

[0040] Inhibitor: 1-ethynylcyclohexanol, brand name YZJ-1, Guangzhou Siyou New Material Technology Co., Ltd.

[0041] Catalyst: platinum catalyst, brand DC-3000, Dongguan Dongsheng Synthetic Materials Co., Ltd.;

[0042] Thermal conductive powder #1: spherical alumina with a D50 of 5 μm, brand name GD-SLQ0050, Guangdong Jinge New Materials Co., Ltd.; spherical alumina with a D50 of 40 μm, brand name BAK-40, Shanghai Baitu High-tech Materials Co., Ltd.; spherical alumina with a D50 of 70 μm, brand name BAK-70, Shanghai Baitu High-tech Materials Co., Ltd., the compounding ratio is 40:30:30;

[0043] Thermal conductive powder #2: D50 is 1μm quasi-spherical alumina, brand NSM-2S, Shanghai Baitu High-tech Materials Co., Ltd.; D50 is 5μm spherical aluminum nitride, brand LG005, Fujian Zhenjing New Materials Technology Co., Ltd.; D50 is 40μm spherical alumina, brand HNA-40, Shanghai Baitu High-tech Materials Co., Ltd.; D50 is 90μm spherical alumina, brand SLA-90, Anhui Yishitong Materials Technology Co., Ltd.; D50 is 100μm spherical alumina, brand HNA-120, Shanghai Baitu High-tech Materials Co., Ltd., the compound ratio is 15:30:25:20:10.

[0044] The preparation methods used in the embodiments of the present invention and the comparative examples include the following steps:

[0045] The components except the catalyst are weighed and mixed evenly according to weight, and finally the catalyst is added and mixed evenly. After vacuuming for 0.5-2 hours, the thermal conductive gasket is obtained after calendering and baking at 120-150° C. for 0.5-1 hour.

[0046] 2. Various performance test methods

[0047] (1) Hardness test: According to ASTM-D2240-2015 standard, use GS-754G Shore00 Japanese Delo brand hardness tester for testing;

[0048] (2) Thermal conductivity test: According to ASTM-D5470-2017 standard, the test was carried out using the DRL-III series thermal conductivity tester of Xiangtan Instrument Co., Ltd.

[0049] (3) 90° peel force test: According to GB / T 2792-2014 standard, the LY-1065A computerized peel force tester of Guangdong Liyi Technology Co., Ltd. was used to test the 90° peel force between the 25 μm thick PET original film and the surface of the thermal conductive pad.

[0050] Table 1 Technical solutions and effects of the embodiments (unit: weight parts)

[0051]

[0052] Table 2 Comparative Examples Technical Scheme and Effects (Units are parts by weight)

[0053]

[0054]

[0055] In Examples 1-6, vinyl silicone oil, MQ silicone resin, hydrogenated silicone oil, inhibitors, thermally conductive powders and catalysts were simultaneously introduced, and the thermally conductive gaskets obtained all achieved increased surface viscosity while maintaining high thermal conductivity, wherein the thermal conductivity coefficient could reach 2.9 W / (m·K) or above, and the 90° peeling force from the original PET film surface was higher than 2.0 gf / mm, and the hardness of the thermally conductive gasket was also increased.

[0056] Comparative Examples 1-2 are all compared with Example 1. Comparative Example 1 does not add MQ silicone resin, and Comparative Example 2 adds too much MQ silicone resin. The 90° peeling force of the obtained thermally conductive pad and the original PET film surface is significantly reduced. It can be seen that different amounts of MQ silicone resin added have different effects on the surface viscosity of the thermally conductive pad. The higher the amount added, the lower the surface viscosity increases. This is mainly because when the addition is just started, the hydroxyl group of the MQ silicone resin is added to the system, which increases the surface viscosity. Continue to increase the amount of MQ silicone resin, and the cross-linking density of the system increases rapidly, resulting in a large change in its hardness, thereby reducing the surface viscosity. It can be seen from Example 4 and Example 2 that when the amount of MQ silicone resin added to the organic phase is the same, the more the amount of thermally conductive powder added, the lower the surface viscosity will be. By comparing Example 4 with Comparative Example 3, it can be seen that Example 4 adds MQ silicone resin, and the surface viscosity can be significantly improved, further illustrating that MQ resin can improve the surface viscosity of the thermally conductive pad. Therefore, Comparative Examples 1-3 cannot achieve good thermal conductivity and suitable surface viscosity at the same time, and cannot achieve the unity of the two.

[0057] Based on the test data of thermal conductivity, hardness and 90° peeling force of the thermally conductive gasket with the PET original film surface in Tables 1 and 2, the thermally conductive gaskets prepared by Examples 1-6 have obvious advantages over the comparative examples and can effectively meet the high standards of customers and the market.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A thermally conductive pad with surface adhesion enhancement, characterized in that: By weight, it includes the following components:

2. The thermally conductive pad according to claim 1, characterized in that: The vinyl silicone oil is any one or more of double-ended vinyl silicone oil, single-ended vinyl silicone oil, and end-side vinyl silicone oil.

3. The thermally conductive pad according to claim 1, characterized in that: The viscosity of the vinyl silicone oil is 100-1000 mPa·s.

4. The thermally conductive pad according to claim 1, characterized in that: The chemical structural formula of the MQ silicone resin is as follows: Wherein, R is any one or more of vinyl, phenyl, hydrogen or methyl.

5. The thermally conductive pad according to claim 1, characterized in that: The hydrogen-containing silicone oil is any one or more of terminal hydrogen-containing silicone oil and side hydrogen-containing silicone oil.

6. The thermally conductive pad according to claim 1, characterized in that: The thermally conductive powder is any one or more combinations of aluminum oxide, aluminum hydroxide, aluminum nitride, and boron nitride.

7. The thermally conductive pad according to claim 1, characterized in that: The mass ratio of the vinyl silicone oil to the MQ silicone resin is 1:(0.12-0.4).

8. The thermally conductive pad according to claim 7, characterized in that: The mass ratio of the vinyl silicone oil to the MQ silicone resin is 1:(0.28-0.35).

9. The method for preparing the thermally conductive gasket according to any one of claims 1 to 8, characterized in that: The steps include: The components other than the catalyst are weighed by weight and mixed evenly, and finally the catalyst is added and mixed evenly, and after vacuuming, the surface-adhesive thermal conductive pad is obtained through calendering and baking.

10. Application of the thermally conductive pad according to any one of claims 1 to 8 in electronic appliances and automobile manufacturing.